(untitled) (Italian Journal of Public Health, 2004)
The smoked mozzarella and caciocavallo cheeses occupy a significant area among the traditional products in the Campania region. Smoked and non-smoked mozzarella and caciocavallo cheeses were screened for the presence of polycyclic aromatic hydrocarbons (PAHs). Total PAH concentration in non-smoked mozzarella ranged from 59.11 to 160.05 μg kg-1 wet weight (w.w.) and in that smoked from 67.49 to 399.90 μg kg-1 w.w. The total PAH content in non-smoked caciocavallo was between 36.70 and 248.59 μg kg-1 w.w.; in the smoked cheese, it varied from 72.52 to 1643.18 μg kg-1 w.w. The benzo(a)pyrene (BaP) values in all cheeses smoked by liquid smoke were higher than the permissible limit for BaP of 0.03 μg kg-1 for foods aromatised with liquid smoke.